2016
DOI: 10.1021/acs.chemrestox.6b00083
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Function Studies of Naphthalene, Phenanthrene, Biphenyl, and Their Derivatives in Interaction with and Oxidation by Cytochromes P450 2A13 and 2A6

Abstract: Naphthalene, phenanthrene, and biphenyl and their derivatives having different ethynyl, propynyl, butynyl, and propargyl ether substitutions were examined for their interaction with and oxidation by cytochromes P450 (P450) 2A13 and 2A6. Spectral interaction studies suggested that most of these chemicals interacted with P450 2A13 to induce Type I binding spectra more readily than with P450 2A6. Among the various substituted derivatives examined, 2-ethynylnaphthalene, 2-naphthalene propargyl ether, 3-ethynylphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 46 publications
2
38
0
Order By: Relevance
“…6C) and 2A6 (Fig. 6D) (26,(28)(29)(30). All of these chemicals induce type I binding spectra with CYP2A13 having high affinities with 2-ethynylnaphthalene, 2-naphthalene propargyl ether, naphthalene, 1-naphthalene ethylpropargyl ether, 2-naphthalene ethylpropargyl ether, 3-ethynylnaphthalene, 9-ethynylnaphthalene, 3-(1-propynyl)phenanthrene, 2-ethynylnaphthalene, 2-(1-propynyl)phenanthrene, phenanthrene, 4-biphenyl propargyl ether, biphenyl, and 4-ethynylbiphenyl (Fig.…”
Section: Fig 2 Effects Of Preincubation Time On Inhibition Of Cyp1amentioning
confidence: 93%
See 4 more Smart Citations
“…6C) and 2A6 (Fig. 6D) (26,(28)(29)(30). All of these chemicals induce type I binding spectra with CYP2A13 having high affinities with 2-ethynylnaphthalene, 2-naphthalene propargyl ether, naphthalene, 1-naphthalene ethylpropargyl ether, 2-naphthalene ethylpropargyl ether, 3-ethynylnaphthalene, 9-ethynylnaphthalene, 3-(1-propynyl)phenanthrene, 2-ethynylnaphthalene, 2-(1-propynyl)phenanthrene, phenanthrene, 4-biphenyl propargyl ether, biphenyl, and 4-ethynylbiphenyl (Fig.…”
Section: Fig 2 Effects Of Preincubation Time On Inhibition Of Cyp1amentioning
confidence: 93%
“…Our previous studies using umu genotoxicity assay with human P450 enzymes in conjunction with the results obtained from Ames mutagenicity assay and other detection systems reported so far (6,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) have suggested that human CYP1A1, 1A2, 1B1, 2A6, 2A13, 2E1, and 3A4 are major enzymes involved in the activation of various environmental carcinogens including PAHs and tobacco-related nitrosamines (Table 1). In this review, we first describe in vivo studies on the roles of CYP1 and 2A enzymes in the formation of tumors caused by various chemical carcinogens; these are reported using (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: T Shimadamentioning
confidence: 99%
See 3 more Smart Citations